2007
DOI: 10.1128/jcm.01578-06
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Real-Time PCR Assay To Detect Treponema pallidum in Clinical Specimens and Assessment of the Assay's Performance by Comparison with Serological Testing

Abstract: The incidence of infectious syphilis in men who have sex with men and human immunodeficiency virus-infected patients has increased steadily in Victoria, Australia, since 2002. A TaqMan real-time PCR assay targeting the polA gene of Treponema pallidum (TpPCR) was developed. The analytical sensitivity of the assay was estimated to be 1.75 target copies per reaction. Initially, the assay was used to test a variety of specimens (excluding blood) from 598 patients. Of the 660 tests performed, positive PCR results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 6 publications
5
52
3
4
Order By: Relevance
“…Our results suggest that in early syphilis, the RPR titer magnitude may not be as predictive of NS as it is during the later stages of disease, and it probably should not be used as the sole criterion for deciding whether to perform an LP. Several studies have evaluated PCR for the diagnosis of NS in adults (10,19,(22)(23)(24)(25)(26)(27)(28)(29). However, the results obtained in these studies are difficult to compare to our results for several reasons.…”
Section: Discussioncontrasting
confidence: 53%
“…Our results suggest that in early syphilis, the RPR titer magnitude may not be as predictive of NS as it is during the later stages of disease, and it probably should not be used as the sole criterion for deciding whether to perform an LP. Several studies have evaluated PCR for the diagnosis of NS in adults (10,19,(22)(23)(24)(25)(26)(27)(28)(29). However, the results obtained in these studies are difficult to compare to our results for several reasons.…”
Section: Discussioncontrasting
confidence: 53%
“…La DFA-TP es un método de gran sensibilidad y especifi cidad pero el reactivo que requiere no está disponible para los laboratorios de diagnóstico, sino que sólo para los laboratorios de referencia 19 . Debido a las limitaciones de los métodos disponibles en la actualidad, el diagnóstico de sífi lis es poco especí-fi co. En este contexto, se ha planteado el uso de NAATs basados en la reacción de la polimerasa en cadena (RPC) para la detección de T. pallidum [20][21][22] . Estos tests se basan principalmente en la detección de dos genes: el gen tpN47 que codifi ca para la proteína de membrana de 47 kDa [22][23][24][25][26] y el gen polA que codifi ca para la ADN polimerasa I 21,27 .…”
Section: Unidad De Infectología (Pvt)unclassified
“…Debido a las limitaciones de los métodos disponibles en la actualidad, el diagnóstico de sífi lis es poco especí-fi co. En este contexto, se ha planteado el uso de NAATs basados en la reacción de la polimerasa en cadena (RPC) para la detección de T. pallidum [20][21][22] . Estos tests se basan principalmente en la detección de dos genes: el gen tpN47 que codifi ca para la proteína de membrana de 47 kDa [22][23][24][25][26] y el gen polA que codifi ca para la ADN polimerasa I 21,27 . La RPC dirigida al gen de la proteína de 47 kDa se ha utilizado ampliamente para detectar T. pallidum en distintos tejidos, mostrando sensibilidades similares al RIT en muestras de úlceras genitales y en sangre total 15,23 .…”
Section: Unidad De Infectología (Pvt)unclassified
“…Real-time PCR was performed in genital lesion specimens, but not in serum. When compared with serology results, polA gene real-time PCR presented the sensitivity of 80.39% and the specificity of 98.40% (Leslie et al, 2007). Another study found sensitivity of 72.8% and specificity of 95.5% in patients with clinical diagnosis of primary syphilis, the detection of secondary syphilis was low, and the sensitivity was 43.0% (Heymans et al, 2010).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Another study found positivity ratio of 39.1% for ttp47 PCR (260 bp) and 31.1% for polA PCR (378 bp), in blood samples from patients with latent syphilis (Castro et al, 2007). The real-time PCR had been developed for detection of T.pallidum DNA in clinical samples, they targeted polA gene (Heymans et al, 2010;Koek et al, 2006;Leslie et al, 2007) or tpp47 gene (Gayet-Ageron et al, 2009). The first test was validated using an analytical panel (n = 140) and a clinical panel of genital samples (n = 112) from patients attending a sexually transmitted infections clinic.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%